(untitled) (Brazilian Journal of Health Research, 2019)
Introduction: Multiple sclerosis is a chronic neurological disease of autoimmune inflammatory nature that leads to functional impairment. Fatigue is a common symptom in patients with multiple sclerosis; it is characterized by symptoms such as tiredness or weakness, energy loss or exhaustion that do not improve after rest. Objective: Evaluating fatigue manifestations and levels in adult patients with multiple sclerosis. Methods: Cross-sectional descriptive study conducted with adult individuals with multiple sclerosis. A sociodemographic and clinical questionnaire and two fatigue symptom assessment questionnaires - the Neurological Fatigue Index for Multiple Sclerosis (NFI-MS) and the Fatigue Severity Scale (FSS) - were used in the current study. The study was performed at Goiânia Multiple Sclerosis Association, Goiânia City-Goiás State. Results: Participants comprised 45 individuals with multiple sclerosis; most of them were women and 53.3% were younger than 40 years. Relapsing-remitting multiple sclerosis was the clinical form most often observed. There was high fatigue manifestation rate among participants, 88.9% according to the FSS and 84.4% according to the NFI-MS; there was significant difference between groups with, and without, fatigue (p <.001). Based on the FSS assessment, 31.1% of participants presented severe fatigue. Participants who did not work, who considered themselves anxious, and who were undergoing, or had undergone, psychological treatment recorded the highest fatigue scores. Conclusion: Individuals with multiple sclerosis present significant manifestation of fatigue symptoms, a fact that indicates the need of making interventions focused on controlling anxiety and psychological disorders, as well as to conduct in-depth investigations about the role played by work in fatigue manifestation.